Efficiency analysis of a solar photovoltaic array coupled with an electrolyser power unit: a case study. Issue 3 (3rd April 2017) - Shiroudi, Abolfazl; Deleuze, Michael S.; Mousavifar, Seyed Ahmad
ABSTRACT: Hydrogen as an energy carrier is one of the most potential candidates for clean energy and can be produced by water electrolysis. The use of 10 kW photovoltaic arrays for supplying a 5 kW electrolyser which consists of 10 series-connected electrolyser stacks and a 28% alkaline (KOH) solution electrolyte has been investigated at the Taleghan renewable energies site in Iran. The hydrogen produced by the electrolyser provides energy for the 1 kW polymer electrolyte membrane fuel cell, which meets the load when the solar energy is insufficient. Variations of the solar radiation intensity, the hydrogen production rate, the solar hydrogen efficiency and the overall efficiency of the solar hydrogen energy unit were monitored in detail. The overall energy efficiency was found to range from 0.93% to 5.01%. The obtained results demonstrate the great potential of such a power system for producing and storing energy in a solar-belt country like Iran.